161k views
4 votes
Simplify –6(5x + 1) + 3(2x – 4).

A.
–30x – 6
B.
6x – 12
C.
–24x – 18
D.
5x – 12

User Mavaze
by
6.3k points

2 Answers

2 votes
i believe the answer is A
User Kfrosty
by
6.7k points
4 votes
Multiply the coefficients to the terms in parentheses:


-6(5x + 1) = (-6 * 5x) + (-6 * 1) = -30x - 6


3(2x - 4) = (3 * 2x) + (3 * -4) = 6x - 12


(-30x - 6) + (6x - 12)

Combine like terms:


-30x + 6x = -24x


-6 + -12 = -18


-24x - 18

The answer is C. -24x - 18.

User Anton Soradoi
by
6.5k points